Strategic factor markets, scale free resources, and economic performance: The impact of product market rivalry - Asmussen, Christian Geisler (Strategic Management Journal, 2015)
This paper analyzes how scale free resources, which can be acquired by multiple firms simultaneously and deployed against one another in product market competition, will be priced in strategic factor markets, and what the consequences are for the acquiring firms' performance. Based on a game‐theoretic model, it shows how the impact of strategic factor markets on economic profits is influenced by product market rivalry, preexisting competitive (dis)advantages, and the interaction of acquired resources with those preexisting asymmetries. New insights include the result that resource suppliers will aim at (and largely succeed in) setting resource prices so that the acquiring firms earn negative strategic factor market profits—sacrificing some of their preexisting market power rents—by acquiring resources that they know to be overpriced . Copyright © 2014 John Wiley & Sons, Ltd.